FOOD PROCESSING AND PACKAGING TECHNOLOGY INNOVATIONS IN FOOD WASTE REDUCTION: A SYSTEMATIC REVIEW - Adityas Agung Ramandani; Eko Risdianto; Fadillah Eka Nuranisa (CV. Media Inti Teknologi, 2025)
Background of study: Food waste is a critical global issue with significant economic, environmental, and social impacts. Approximately one-third of all food produced is wasted, contributing to over 3.3 billion tons of CO2 emissions annually and wasting 250 cubic kilometers of water each year. This systematic literature review (SLR) aims to explore recent innovations in food processing and packaging technologies that contribute to food waste reduction. Methods: Pendekatan yang digunakan dalam penelitian ini adalah Systematic Literature Review (SLR) dengan mengikuti pedoman PRISMA. Artikel-artikel yang relevan diidentifikasi, disaring, dan dianalisis dari berbagai database seperti Scopus. Analisis bibliometrik dan visualisasi dilakukan menggunakan aplikasi VOSviewer dan Biblioshiny untuk memetakan tren penelitian, kolaborasi, serta fokus tematik dalam bidang ini. A total of 127 articles were analyzed, revealing the latest trends in food packaging and processing innovations. The review includes studies on active and biodegradable packaging materials, as well as consumer behavior interventions that influence food waste reduction. Result: 62.5% of studies focused on developing active and biodegradable packaging materials. Notable examples include the use of chitosan-based films that extended the shelf life of fresh produce by up to 10 days, and the application of antimicrobial packaging that reduced spoilage rates by 25% in perishable foods. 25% of studies reviewed behavioral interventions, such as consumer education campaigns that led to a 15% reduction in food waste in households. Innovations such as bio-based polymers and smart packaging have shown significant potential in minimizing food spoilage during transport and storage Conclusion: The findings highlight the potential of material innovations in food packaging, but research gaps remain in scaling these technologies for industrial application and integrating them with consumer behavior strategies. Future research should focus on optimizing material properties for large-scale production, evaluating safety and toxicity, and exploring policy frameworks that incentivize the adoption of sustainable packaging solutions. This review underscores the need for cross-sector collaboration to drive impactful changes in food waste reduction and achieve sustainability goals.